2003
DOI: 10.1002/bem.10166
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency (RF) effects on blood cells, cardiac, endocrine, and immunological functions

Abstract: Effects of radiofrequency electromagnetic fields (RFEMF) on the pituitary adrenocortical (ACTH), growth (GH), and thyroid (TSH) hormones have been extensively studied, and there is coherent research on reproductive hormones (FSH and LH). Those effects which have been identified are clearly caused by heating. The exposure thresholds for these effects in living mammals, including primates, have been established. There is limited evidence that indicates no interaction between RFEMF and the pineal gland or an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 40 publications
2
35
0
3
Order By: Relevance
“…While there was an increase in the cell decomposition which affect the flow of potassium ions from red blood cells of rabbits that were exposed to electromagnetic waves, which indicates the strength of cells carry the blood of humans to high temperature and adaptability, however, while not tolerate blood cells rabbit this increase caused by heating and exposure to electromagnetic waves, which reported with many of the scientists and the actual impact of the hard electromagnetic waves is the effect of heat raises the temperature of the tissue [46]. This is consistent with Black & Heynik [47] who found that did not caused changes, clear decomposition of the red blood cells and did not increase the temperature as well as the sensitivity of the white blood cells when exposed to electromagnetic waves. Stronati, et al [48] reported that the lack of any damage to the cells of human blood or genetic mutations of blood when exposed to 50 Hz frequency or 60 Hz for 24 hours, while in some cases there may provoke the onset of these mutations.…”
Section: Discussionsupporting
confidence: 72%
“…While there was an increase in the cell decomposition which affect the flow of potassium ions from red blood cells of rabbits that were exposed to electromagnetic waves, which indicates the strength of cells carry the blood of humans to high temperature and adaptability, however, while not tolerate blood cells rabbit this increase caused by heating and exposure to electromagnetic waves, which reported with many of the scientists and the actual impact of the hard electromagnetic waves is the effect of heat raises the temperature of the tissue [46]. This is consistent with Black & Heynik [47] who found that did not caused changes, clear decomposition of the red blood cells and did not increase the temperature as well as the sensitivity of the white blood cells when exposed to electromagnetic waves. Stronati, et al [48] reported that the lack of any damage to the cells of human blood or genetic mutations of blood when exposed to 50 Hz frequency or 60 Hz for 24 hours, while in some cases there may provoke the onset of these mutations.…”
Section: Discussionsupporting
confidence: 72%
“…Meanwhile, in the experiment with rats, Black and Heynick [21] observed no effect of 2450 MHz EMF on T 4 levels. The effect of weak electromagnetic fields (ELF EMF) (50 Hz) on blood iodothyronine concentration of chick embryos was also investigated by Sechman et al [22], who demonstrated that ELF EMF significantly elevate the levels of T 4 (between 11th and 18th day of incubation) and T 3 (between 18th day of incubation and hatching) in the blood of the analyzed birds.…”
Section: Discussionmentioning
confidence: 93%
“…Leucocytes are much more sensitive than erythrocytes. Black and Heynick [41] reported that exposure to radiofrequency electromagnetic fields can stimulate lymphocytes to become lymphoblasts (active cells undergoing mitosis). Although present findings indicate a significant increase in blood cell counts following microwave radiations, mechanism of such increase and its pathology needs to be confirmed before drawing meaningful conclusion.…”
Section: Discussionmentioning
confidence: 99%